Exploring the Antimicrobial Potential of a Peptide Against Mixed Biofilm of Staphylococcus aureus and Candida albicans - Sandim, Graziela Custódia; Sardi, Janaina de Cássia Orlandi; da Silva, Amanda Carolina Borges; Lima, Leticia Souza; Parisotto, Eduardo Benedetti; Junior, Edson Crusca [UNESP]; Jacobowski, Ana Cristina; Macedo, Maria Ligia Rodrigues (Springer Nature, 2025)
Candida albicans and Staphylococcus aureus species are, respectively, the most common fungal and bacterial agents isolated from bloodstream infections worldwide. In addition, 20% of all C. albicans bloodstream infections have been shown to be polymicrobial in nature, and the bacterium Staphylococcus aureus is the third most common co-isolated organism. Finding an efficient treatment strategy for polymicrobial infections is a major challenge, as traditional therapies most often target only individual agents within specific realms. Thus, the present study investigated the antimicrobial and anti-biofilm polymicrobial activity of the peptide ITR-16, a new synthetic peptide against microorganisms with a high incidence in nosocomial infections. This peptide was tested against S. aureus and C. albicans in planktonic form and mono and polymicrobial biofilm. Synergism assays with other common antimicrobials were performed. The ITR-16 peptide was also tested for its preliminary acute toxicity in an in vivo model of Galleria mellonella. The ITR-16 peptide showed antimicrobial activity, with minimal inhibitory concentrations (MICs) ranging from 0.62 to 2.5 µM. And treatment with ITR-16 at 10 × MIC significantly reduced biofilm formation and viability of S. aureus and C. albicans strains in both monospecies and polymicrobial biofilms. Furthermore, it demonstrated low toxicity in the G. mellonella model at anti-biofilm concentrations. These results present a new molecule with potential polymicrobial anti-biofilm activity.